2004
DOI: 10.1002/cne.20280
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and innervation patterns of dopaminergic, noradrenergic, and serotonergic neurons in larval zebrafish

Abstract: We report the development of aminergic neurons from 0-10 days postfertilization (dpf) in zebrafish (Danio rerio). This study was prompted by the lack of information regarding patterns of spinal aminergic innervation at early stages, when the fish are accessible to optical, genetic, and electrophysiological approaches toward understanding neural circuit function. Our findings suggest that aminergic populations with descending processes are among the first to appear during development. Descending aminergic fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
272
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(308 citation statements)
references
References 68 publications
(100 reference statements)
32
272
1
Order By: Relevance
“…Recent studies demonstrated that DA modulates Akt signaling in the adult rodent and primate striatum, which is associated with regulating motor control (Beaulieu et al, 2004(Beaulieu et al, , 2005. Although our study focused on early larval stages, the larval pattern of DA circuitry in zebrafish is comparable to the adult pattern (McLean and Fetcho, 2004), suggesting that this pattern of DA-dependent Akt modulation is maintained in adulthood. However, future investigations are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recent studies demonstrated that DA modulates Akt signaling in the adult rodent and primate striatum, which is associated with regulating motor control (Beaulieu et al, 2004(Beaulieu et al, , 2005. Although our study focused on early larval stages, the larval pattern of DA circuitry in zebrafish is comparable to the adult pattern (McLean and Fetcho, 2004), suggesting that this pattern of DA-dependent Akt modulation is maintained in adulthood. However, future investigations are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 80%
“…Several components of the DA biosynthetic and signaling pathways are expressed in the zebrafish larval brain (Holzschuh et al, 2001;Boehmler et al, 2004Boehmler et al, , 2007McLean and Fetcho, 2004;Anichtchik et al, 2006;Li et al, 2007), but which intracellular pathways are modulated by DA and its role in mediating behavior, as well as how DA signaling regulates zebrafish brain development, is not well characterized. Previous studies have demonstrated that DA is involved in larval motor regulation and that this is mediated, in part, by cAMP signaling (Boehmler et al, 2007;Thirumalai and Cline, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of tphD1, one of the three tryptophan hydroxylases in zebrafish, was previously reported in the subset of the inner nuclear layer neurons (Bellipanni et al 2002). Serotonin was detected in the medulla oblongata of zebrafish embryo (McLean and Fetcho 2004a). Given that both serta and sertb are functional, the sum of the expression pattern of two genes should reflect the cells harboring the serotonin transporter activity in zebrafish.…”
Section: Expression Of Sert During Zebrafish Development In Comparisomentioning
confidence: 73%
“…These findings raise two questions: first, what drives spike activity in the population of neurons that is not affected by GABA or glutamate receptor antagonists? Amine and peptide neurotransmitters are also expressed at early stages of development (Lauder et al, 1981;Hu et al, 2001;McLean and Fetcho, 2004) and are candidates to evaluate. Second, what is the function of calcium spike activity in these neurons if it does not regulate the expression of GABA, glutamate, glycine or acetylcholine?…”
Section: Discussionmentioning
confidence: 99%